Pengaruh Transfer Pricing, Leverage, Dan Profitabilitas Terhadap Tax Avoidance Pada Perusahaan Sub Sektor Makanan Dan Minuman BEI Tahun 2018-2021 - Adelia, Cantika; Asalam, Ardan Gani (Politeknik Ganesha Medan, 2024)
Tax avoidance is a tax avoidance effort that is carried out legally and safely for taxpayers because it does not conflict with tax provisions. the purpose of this study is to analyze the effect of transfer pricing, leverage, and profitability on tax avoidance case studies in food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2018-2021. The data obtained in this study comes from the annual reports of food and beverage sub-sector companies listed on the IDX for 2018-2021. The technique used in this study was purposive sampling and obtained 18 companies with a 4-year research period, namely 2018-2021, so that 72 samples were obtained. The analytical method used in this study was panel data regression analysis which was processed using eviews version 12. The results of testing with the panel data regression method show that the transfer pricing variable has no effect on tax avoidance, while leverage and profitability have a positive effect on tax avoidance.